The intersection of school, diversity and intercultural dialogues: second generation Brazilians and Cape Verdeans in the Lisbon metropolitan area - Barroso Hortas, Maria João (2019)
This paper focuses on schools in the inner city of the Lisbon metropolitan area and a suburban neighbourhood located in the municipality of Sintra, where second generation Brazilian and Cape Verdean students adhere to different meanings of diversity and intercultural dialogue. Their experiences and interpretations were examined more closely through the use of several methods: (1) a multi-level questionnaire which was directed at both students and parents, (2) a compilation of qualitative statements provided by students and parents and (3) a collection of qualitatively analysed statements from teachers and school board members. The results indicate there is a wide divergence of attitudes and perspectives among the different actors, showing a disparity of perspectives when addressing intercultural education. The conclusions drawn indicate that promoting intercultural dialogue is not a one-way street, but requires the development of several intertwined strategies in each of these different contexts and communities. The observed practices of teachers, students, and administrators fell short of the expected policies incorporating intercultural education, indicating that the main barrier for educating these second generation youth is the lack of professional commitment and dialogue between teachers, students and families. Recommendations to foster high-quality intercultural education are identified.